2017
DOI: 10.1523/jneurosci.2606-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Attention Is Required for Knowledge-Based Sequential Grouping: Insights from the Integration of Syllables into Words

Abstract: How the brain groups sequential sensory events into chunks is a fundamental question in cognitive neuroscience. This study investigates whether top-down attention or specific tasks are required for the brain to apply lexical knowledge to group syllables into words. Neural responses tracking the syllabic and word rhythms of a rhythmic speech sequence were concurrently monitored using electroencephalography (EEG). The participants performed different tasks, attending to either the rhythmic speech sequence or a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 80 publications
10
94
2
Order By: Relevance
“…While recent research suggests that processing of information contingent on successful word recognition is suppressed for unattended speech [12,14], these previous findings leave open the possibility that unattended speech is processed up to and including identification of lexical items, but without retrieval of the recognized words’ properties. The results presented here indicate that lexical processing of unattended speech is suppressed at the level of detecting word forms.…”
Section: Resultsmentioning
confidence: 98%
“…While recent research suggests that processing of information contingent on successful word recognition is suppressed for unattended speech [12,14], these previous findings leave open the possibility that unattended speech is processed up to and including identification of lexical items, but without retrieval of the recognized words’ properties. The results presented here indicate that lexical processing of unattended speech is suppressed at the level of detecting word forms.…”
Section: Resultsmentioning
confidence: 98%
“…Many previous studies have shown that attention can modulate neural entrainment (e.g., Calderone et al, 2014;Lakatos et al, 2013;Golumbic et al, 2013;Ding & Simon, 2012). Importantly, Ding et al (2018) found that attention to a speech stimulus is required in order for neural tracking beyond the syllable envelope to be observed, suggesting that combining syllables into words and phrases requires attention.…”
Section: Discussionmentioning
confidence: 95%
“…A large body of research has shown that neural populations closely align their phase ("entrain") to the envelope of the speech signal, which correlates with the syllable rate (see, e.g., Peelle & Davis, 2012;Zoefel & VanRullen, 2015 for comprehensive reviews). In fact, information conveyed at the syllable frequency constitutes the acoustically most prominent timescale in the signal (Ding et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The capability and limitations for parallel speech processing have been the focus of long-standing theoretical debates. However, much of this has been fueled by Selective Attention studies focusing on whether so-called unattended speech is processed (Beaman et al, 2007;Ding et al, 2018;Driver, 2001;Lachter et al, 2004;Röer, Körner, Buchner, & Bell, 2017;Wood & Cowan, 1995). The use of a Distributed Attention paradigm, as used here, provides a substantially more direct way for evaluating the ability and limitations of encoding, processing and responding to concurrent speech.…”
Section: The Comparison Between Selective and Distributed Attention Imentioning
confidence: 99%